Choking on a foreign body: a physiological study of the effectiveness of abdominal thrust manoeuvres to increase thoracic pressure. Issue 6 (12th April 2017) - Pavitt, Matthew J; Swanton, Laura L; Hind, Matthew; Apps, Michael; Polkey, Michael I; Green, Malcolm; Hopkinson, Nicholas S
Abstract : The Heimlich manoeuvre is a well-known intervention for the management of choking due to foreign body airway occlusion, but the evidence base for guidance on this topic is limited and guidelines differ. We measured pressures during abdominal thrusts in healthy volunteers. The angle at which thrusts were performed (upthrust vs circumferential) did not affect intrathoracic pressure. Self-administered abdominal thrusts produced similar pressures to those performed by another person. Chair thrusts, where the subject pushed their upper abdomen against a chair back, produced higher pressures than other manoeuvres. Both approaches should be included in basic life support teaching.